Electronic Student Worksheets Based on Rigorous Mathematical Thinking for Sequence and Series Materials in Senior High School - Hutami Sukma Hayati; Puji Astuti; Febrian Febrian (Jurnal Gantang, 2022)
The rapid development of technology must be utilized as well as possible, especially in the world of education, because education is the basis for forming individuals who are strong and able to compete in facing the challenges of the times. The habit of students using existing formulas without knowing the concept of the material causes them to have difficulty solving the same problem but in a different form of problem. Therefore, the development of electronic student worksheets based on Rigorous Mathematical Thinking (RMT) on the material of rows and series becomes an electronic teaching material that contains the stages of the learning process to build an in-depth understanding of the concepts of students as well as being one of the changes from existing technological developments. This study aimed to assess the validity and practicality of electronic student worksheets based on RMT developed. The research method used is Research and Development (R&D) with the 4D development model. The validity and practicality assessment instrument is a student questionnaire sheet with a Likert scale. The data obtained were analyzed using the percentage of the assessment score. The validation results show that electronic student worksheets are categorized as valid, with an average percentage of material validation of 88.13%, an average percentage of media validation of 94.62%, and an average percentage of language validation 93.64%. The practicality test obtained an average percentage of 78.39% in the practical category.